β symmetry of heterotic supergravity - Baron, Walter Helmut (2025)
The low energy effective action describing the Kaluza-Klein reduction of string theory on a d-torus possesses a continuous O(d, d) global symmetry. The non-geometric piece of this symmetry, parameterized by a bi-vector β, was recently shown to effectively act as a hidden symmetry on the massless RR and universal NSNS fields of the ten dimensional parent theory, fixing their couplings. Here we extend the analysis of this symmetry to the massless gauge and fermion fields of heterotic supergravity. While the interactions of the boson fields are univocally fixed by β symmetry, we find four bilinear and two quartic β invariant combinations of fermions whose relative coefficients in the action must be determined by supersymmetry. Although not fully fixed, bilinear and quartic fermion couplings are strongly restricted by β symmetry at leading order in α ′ .